Trends in female education in low- and middle-income countries: Coherence across data sources - Kristen Jeffers; Albert Esteve (Comparative Population Studies (CPoS), 2022)
Educational expansion and the closing of gender gaps in education are key objectives in national and international policy agendas. Monitoring progress towards these goals requires comparable data across countries and over time. The availability of international census and survey microdata allows for cross-national comparisons of education participation and completion. However, we lack systematic analyses of how trends vary across data sources and of the extent to which these data sources offer a consistent account of progress in education. In this paper, we examine coherence in estimates of educational attainment among women aged 25 to 29 in 75 countries across the three main repositories of international population microdata: IPUMS International, the Demographic and Health Surveys (DHS) and the Multiple Indicator Cluster Surveys (MICS). Coherence analysis of 535 census and sur vey obser vations from 1960 to 2017 shows high levels of consistency overall but also identi fi es observations misaligned with trends. Results provide practical information to the research community about the validity of comparative investigations using three important data sources for demographic studies. The data also serve as benchmarks for assessing the quality of education information obtained in data sources not included in our analysis and the trend alignment of future estimates.
urn:nbn:de:bib-cpos-2022-14en6
Keywords: 300; Educational expansion; Census microdata; DHS; MICS; Data coherence